VD_FINDINFO Décision / 2018 / 601 vom 3. Juli 2018 - VD Tribunal cantonal (2018)
LÉSION CORPORELLE GRAVE, NÉGLIGENCE, DILIGENCE, DÉPENS | 125 CP, 319 al. 1 CPP (CH), 319 CPP (CH), 429 CPP (CH), 433 CPP (CH)